2014
DOI: 10.1007/978-3-319-11038-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biofilm Development on Neonatal Enteral Feeding Tubes

Abstract: Neonates in intensive care units often require supporting medical devices and antibiotic treatment. The intensive care treatment combined with their immature immune system, the increased permeability of mucosa, and the undeveloped microflora of the gut may render the neonates highly vulnerable to colonisation and subsequent infections when exposed to opportunistic pathogens. These infections may not only be local gastrointestinal infections, but also systematic following translocation from the gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…A wide variety of organisms was recovered from neonatal feeding tubes in studies by Juma and Forsythe 58 and Hurrell et al 59 In Juma and Forsythe's study, some of the organisms were encoded for antibiotic resistance 58 . Hurrell and colleagues reported that a multitude of organisms, including antibiotic‐resistant ones, was identified in 129 feeding tubes collected from 2 neonatal intensive care units (NICUs), and Klebsiella pneumoniae and Serratia marcescens caused infections in the 2 NICUs 59 .…”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
“…A wide variety of organisms was recovered from neonatal feeding tubes in studies by Juma and Forsythe 58 and Hurrell et al 59 In Juma and Forsythe's study, some of the organisms were encoded for antibiotic resistance 58 . Hurrell and colleagues reported that a multitude of organisms, including antibiotic‐resistant ones, was identified in 129 feeding tubes collected from 2 neonatal intensive care units (NICUs), and Klebsiella pneumoniae and Serratia marcescens caused infections in the 2 NICUs 59 .…”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
“…12,13 Kpn strains have the ability to produce biofilms on abiotic surfaces, which is directly associated to hospital-acquired infections, given that structures form, and persist, on indwelling devices. 14,15 Biofilm structures protect Kpn from commonly used disinfectants, antibiotics, and the attack of host immune responses near the site of contact between the human body and the indwelling devices. 16,17 Kpn biofilms formed on abiotic surfaces have been associated with production of type 1 and type 3 fimbriae 4,18,19 and the Escherichia coli common pili (Ecp).…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the study is that the feeding samples could not be analyzed before their pass through the feeding tubes; therefore, environmental contamination, including contamination during OMM collection and/or during delivery of either OMM, donor milk or infant formula cannot be ruled out as a source of S. marcescens in this study. Independently of the original source, feeding tubes are excellent sites for bacterial biofilm formation, preferentially by members of the Family Enterobacteriaceae, and could act as a reservoir of these bacteria in the NICU [26, 2830]. The nasogastric tubes replacement protocol in the hospital was changed after observing the contamination level of the feeding samples [26].…”
Section: Discussionmentioning
confidence: 99%